Transfers and Gifts in OG Models: Monetary Steady States - Christian Ghiglino; Bodil Olai Hansen; Mich Tved (Copenhagen Business School (CBS), Department of Economics, 2000)
In the present paper the study of the welfare effects of endowment transfers is extended to the set of steady states of a general stationary overlapping generation model. A complete characterization of manipulations by coalitions and transfers which leads to welfare paradoxes is provided.
hdl:10398/7611
Keywords: D51; D91; E32; 330; Overlapping-generations models; manipulations; transfer paradox; Leontief effect; steady states; theory of duality